Predicting boycott intention and participation among urban Muslim consumers in Indonesia - Prananta, Widya; Wijaya, Angga Pandu (Faculty of Business & Economics, Universitas Islam Indonesia, 2026)
Purpose – This research aims to extend the classic theory of planned behavior (TPB) framework by incorporating social media influence and religiosity as key predictors, thereby providing a more comprehensive explanation of boycott intention and subsequent participation among Muslim consumers in a high-digital-penetration, Muslim-majority emerging market context. Methodology – A quantitative cross-sectional survey was conducted among 250 Muslim consumers aged 18 years and above in Semarang, Central Java, Indonesia. Respondents were purposively selected based on their recent fast-moving consumer goods (FMCG) purchases and awareness of ongoing boycott campaigns. Data were collected via questionnaires and analyzed using structural equation modeling (PLS-SEM) in SmartPLS 4.0.Findings – The results show that attitudes towards boycotting, perceived behavioral control, and social media influence have a significant positive effect on boycott intention, and the latter has a strong predictive power for actual boycott participation. Social media influence was the most powerful predictor. Religiosity did not significantly moderate boycott intention.Implications – Multinational FMCG companies operating in Muslim-majority emerging markets should prioritize digital reputation management, transparent ethical and halal communication, proactive engagement with social media influencers, and rapid response strategies to mitigate boycott risks. Local brands can leverage digital momentum to strengthen their market position.Originality – This study pioneers the integration of social media influence as a distinct antecedent and religiosity as a moderator within an extended TPB framework in the context of geopolitically motivated boycotts in Indonesia’s digitally advanced Muslim-majority market. The finding that social media influence outweighs religiosity challenges the prevailing assumptions in the Islamic marketing literature.